Structural organization of the human alpha-galactosidase A gene: further evidence for the absence of a 3' untranslated region. - Bishop, D F (1988)
Human alpha-galactosidase A (alpha-D-galactoside galactohydrolase; EC 3.2.1.22) is a lysosomal hydrolase encoded by a gene localized to the chromosomal region Xq22. The deficient activity of this enzyme results in Fabry disease, an X chromosome-linked recessive disorder that leads to premature death in affected males. For studies of the structure and function of alpha-galactosidase A and for characterization of the genetic lesions in families with Fabry disease, the full-length cDNA was isolated, sequenced, and used to screen human genomic libraries. The 1393-base-pair full-length cDNA had a 60-nucleotide 5' untranslated region and encoded a precursor peptide of 429 amino acids including a signal peptide of 31 residues. Three overlapping lambda clones spanning 32 kilobases were identified that contained the entire approximately equal to 12-kilobase chromosomal gene as well as approximately equal to 9 and approximately equal to 11 kilobases of 5' and 3' flanking sequence, respectively. The gene had seven exons. The genomic exonic and full-length cDNA sequences were identical. All intron-exon splice junctions conformed to the GT/AT consensus sequence. The 5' flanking region of this lysosomal housekeeping gene contained Sp1 and CCAAT box promoter elements as well as sequences corresponding to the activator protein 1 (AP1), octanucleotide ("OCTA"), and "core" enhancer elements. There was an upstream "HTF" island (Hpa II tiny fragments) followed by four direct repeats of the "chorion box" enhancer. The unique lack of a 3' untranslated sequence in the alpha-galactosidase A cDNA was confirmed by sequencing additional cDNA clones and the genomic 3' region.